Arthropod biodiversity loss and the transformation of a tropical agro-ecosystem - Perfecto, Ivette (1997)
The coffee (coffea arabica) agro-ecosystem in the Central Valley of Costa Rica was formerly characterized by a high vegetational diversity. This complex system has been undergoing a major transformation to capital-intensive monocultural plantations where all shade trees are eliminated. In this study we examined the pattern of arthropod biodiversity loss associated with this transformation. Canopy arthropods were sampled in three coffee farms: a traditional plantation with many species of shade trees, a moderately shaded plantation with only Erythrina poeppigeana and coffee, and a coffee monoculture. An insecticidal fogging technique was used to sample both canopy and coffee arthropods. Data are presented on three major taxonomic groups: Coleoptera, non-formicid Hymenoptera, and Formicidae. Data demonstrate that the transformation of the coffee agro-ecosystem results in a significant loss of biological diversity of both canopy arthropods as well as arthropods living in coffee bushes. Percentage of species overlap was very small for all comparisons. Furthermore, species' richness on a per tree basis was found to be within the same order of magnitude as that reported for trees in tropical forests. If results presented here are generalizable, this means that conservation efforts to preserve biological diversity should also include traditional agro-ecosystems as conservation units.